# Algebra

Factor:
2x^2 +13x-6
Please give step by step directions. I have tried doing it, but I can't get the right numbers.

Thanks!

1. 👍 0
2. 👎 0
3. 👁 121
1. You know the factors will be among

(2x+?)(x-?)
(2x-?)(x+?)

where the ? can be 2,3 or 1,6

Now you just have to play around till you find what works.

That 13 in the middle is a good indicator that 1,6 will be involved, since it is so big. Now recall that 13 =12+1, so I expect the 6 and 2 will be paired up.

(2x-1)(x+6) = 2x^2+11x-6
Hmmm. Guess not. Maybe it's not so easy.

The discriminant is

b^2-4ac = 169+48 = 217

Whoa! That is not a perfect square, so your quadratic does not factor over the rational numbers. I suspect a typo.

(2x+1)(x+6) = 2x^2+13x+6

Is that better?

1. 👍 0
2. 👎 0

## Similar Questions

1. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

2. ### MATH

Hannah is showing her work in simplifying (6.1 − 4.5) − 2.5 + 3.9. Identify any error in her work or reasoning. Step 1: (6.1 − 4.5) − 2.5 + 3.9 Step 2: 6.1 + (− 4.5 − 2.5) + 3.9 (associative property) Step 3: 6.1 − 7

3. ### math

10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

4. ### math

Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

1. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

2. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

3. ### Help PLZ!!

consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: -4 3 7 + 7 + (-3 4 7 ) Step 1: = -4 3 7 + (-3 4 7 ) + 7 Step 2: = -4 + (- 3 7 ) + (-3) + (- 4 7 ) + 7 Step 3: = -4 + (- 3 7 ) + (-

4. ### Quick math help

In which step below does a mistake first appear in simplifying the expression? 0.5(-12c+6)-3(c+4)+10(c-5) Step 1: -6c+3-3(c+4)+10(c-5) Step 2: -6c+3-3c-12+10(c-5) Step 3: -6c+3-3c-12+10c-50 Step 4: 7c-41 Please help me!!! Thank

1. ### Algebra

Debbie finished her algebra test early so she decided to check each of her answers. After checking her answer to question #10, she realized she made a mistake in her solution. In which step does Debbie make her mistake? Original

2. ### Physics

An arrow is shot straight up from the edge of a cliff with an initial velocity of 50 ft/s. Answer the following questions using English units. The acceleration due to gravity has a magnitude of 32.2 ft/s. A. Find the time to reach

3. ### Math

I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −

4. ### Information Literacy

Please check my answer thank you. 1. Mary is documenting her sources. Which step of the research process is she on ? A. Step 3: Evaluating your sources B Step 5: Cite your sources X C. Step 4: Organize your information D. Step 2: